2017
DOI: 10.1080/13614533.2017.1330219
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Librarians' Role in Supporting Grant Applications and Reducing Waste in Research: Outcomes From a Literature Review and Survey in the NIHR Research Design Service

Abstract: found three examples where librarians were involved: in writing sections of the application; conducting reviews and becoming a co-applicant. We recommend librarians engage with researchers by checking whether search requests are to support an application and by becoming familiar with resources and techniques to support grant proposal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In order to meet the requirements of this extended role, it is recommended that library and information professionals familiarise themselves with the ever increasing variety of review types and associated search requirements defined by their purpose, audience and available resources. In a 2005 case study, Harris () concluded that a ‘deeper understanding’ of research methodologies by librarians contributed to investigators’ ‘increased appreciation for their searching and organizational expertise.’ These benefits remain current, and additional advantages have emerged such as contributing to reducing avoidable waste in research, and becoming more embedded in the research team throughout the review process, not just in the initial planning and information retrieval stage (Edmunds Otter, Wright & King, ). Roles such as ‘systematic review consultant’ are reported in the literature, and one of the common tasks associated with this role is advising on the most appropriate review type for the research question (Foster, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to meet the requirements of this extended role, it is recommended that library and information professionals familiarise themselves with the ever increasing variety of review types and associated search requirements defined by their purpose, audience and available resources. In a 2005 case study, Harris () concluded that a ‘deeper understanding’ of research methodologies by librarians contributed to investigators’ ‘increased appreciation for their searching and organizational expertise.’ These benefits remain current, and additional advantages have emerged such as contributing to reducing avoidable waste in research, and becoming more embedded in the research team throughout the review process, not just in the initial planning and information retrieval stage (Edmunds Otter, Wright & King, ). Roles such as ‘systematic review consultant’ are reported in the literature, and one of the common tasks associated with this role is advising on the most appropriate review type for the research question (Foster, ).…”
Section: Discussionmentioning
confidence: 99%
“…By integrating quantitative aspects to qualitative research, they may add rigour to research (Sheffield, Refolo, Petanceska, & King, 2017). By performing bibliometrics funding analysis, they may support grant applications (Edmunds, Wright, & King, 2017), by using content based and historical bibliometrics they may cooperate in conducting systematic and scoping reviews and support evidence‐based practice in clinical education (Simons, Davidson, & Forrest, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Services provided by health information professionals can also help improve research productivity and quality -in particular knowledge synthesis [27][28][29][30][31], and reduce waste [32][33][34][35]. This is true across healthcare disciplines, including medicine, nursing, rehabilitation etc.…”
Section: Introductionmentioning
confidence: 99%